Thúc đẩy ý định mua thông qua tính chân thực trách nhiệm xã hội của doanh nghiệp: Vai trò trung gian của bản sắc đạo đức và cơ chế điều tiết của hình ảnh quốc gia - Nguyễn Thị Bích, Huệ; Đinh Văn, Hoàng; Nguyễn Thanh, Thảo; Vương Thái, Sơn; Trần Ngọc, Minh; Nguyễn Đình Gia, Hân (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2026)
This study examines the impact of perceived Corporate Social Responsibility (CSR) authenticity on purchase intention, while investigating the mediating role of moral identity and the moderating role of country image. Using a quantitative approach, data were collected from consumers, yielding 384 valid responses, and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that perceived CSR authenticity has a direct and positive influence on purchase intention. Furthermore, moral identity acts as a partial mediator in this relationship, while country image exhibits a significant dual moderating role by strengthening the effect of CSR authenticity on moral identity and moderating the effect of CSR authenticity on purchase intention. These findings contribute to the literature on sustainable consumer behavior and offer practical implications for business practice.